Photodynamic therapy with redaporfin targets the endoplasmic reticulum and Golgi apparatus. (28th May 2018) - Gomes‐da‐Silva, Lígia C; Zhao, Liwei; Bezu, Lucillia; Zhou, Heng; Sauvat, Allan; Liu, Peng; Durand, Sylvère; Leduc, Marion; Souquere, Sylvie; Loos, Friedemann; Mondragón, Laura; Sveinbjørnsson, Baldur; et al.
Abstract: Preclinical evidence depicts the capacity of redaporfin (Redp) to act as potent photosensitizer, causing direct antineoplastic effects as well as indirect immune‐dependent destruction of malignant lesions. Here, we investigated the mechanisms through which photodynamic therapy (PDT) with redaporfin kills cancer cells. Subcellular localization and fractionation studies based on the physicochemical properties of redaporfin revealed its selective tropism for the endoplasmic reticulum (ER) and the Golgi apparatus (GA). When activated, redaporfin caused rapid reactive oxygen species‐dependent perturbation of ER/GA compartments, coupled to ER stress and an inhibition of the GA‐dependent secretory pathway. This led to a general inhibition of protein secretion by PDT‐treated cancer cells. The ER/GA play a role upstream of mitochondria in the lethal signaling pathway triggered by redaporfin‐based PDT. Pharmacological perturbation of GA function or homeostasis reduces mitochondrial permeabilization. In contrast, removal of the pro‐apoptotic multidomain proteins BAX and BAK or pretreatment with protease inhibitors reduced cell killing, yet left the GA perturbation unaffected. Altogether, these results point to the capacity of redaporfin to kill tumor cells via destroying ER/GA function. Synopsis: Redaporfin, a latest generation light‐sensitizing agent employed in photodynamic anti‐tumor therapy, acts via selective damage of endoplasmic reticulum (ER) and Golgi apparatus (GA), leading to reactive oxygen species‐mediated ER stress, compromised protein secretion, and eventually cancer cell death. Redaporfin enriches in the ER and GA in human osteosarcoma cells. Light activated redaporfin causes reactive oxygen species‐dependent perturbation of the ER and GA, coupled to irreversible inhibition of GA function, leading to reduced cytokine secretion. Dissipation of the GA by brefeldin A or golgicide A can reduce the redaporfin‐mediated phototoxicity. Localized production of reactive oxygen species at the GA is sufficient to kill cancer cells. Abstract : The antineoplastic photosensitizer redaporfin kills cancer cells via irreversible inactivation of endoplasmic reticulum and Golgi, paralyzing protein secretion and triggering mitochondrial cell death.